1991
DOI: 10.2307/2418876
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Ranunculaceae Based on Epidermal Microcharacters and Macromorphology

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 150.135.239.97 on Mon,ABSTRACT. The epidermal microcharacters of 20 genera in the Ranunculaceae and 10 outgroup genera from the families Glaucidiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…Caltha is generally considered the most original group of Helleboroideae (Smith 1928;Tamura 1987Tamura , 1990, as also supported in later research (Loconte & Estes 1989;Hoot 1991), and the two trees used in our research gave similar results. Caltha is not closely related to Trollius and these two genera should not be assigned to the same tribe (Xi et al 1993).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Caltha is generally considered the most original group of Helleboroideae (Smith 1928;Tamura 1987Tamura , 1990, as also supported in later research (Loconte & Estes 1989;Hoot 1991), and the two trees used in our research gave similar results. Caltha is not closely related to Trollius and these two genera should not be assigned to the same tribe (Xi et al 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Gu & Ren (2007) found that Coptidoideae was an early clade next to Hydrastis in Ranunculaceae and our results support that place at the base of phylogenetic trees. These authors consider that Hydrastis is a highly autapomorphic lineage that should be retained within the Ranunculaceae, while Hoot (1991) advocates placement of Hydrastis in the monotypic family Hydrastidaceae, closely related to the Ranunculaceae (Delectis Florae Reipublicae Popularis Sinicae Agendae, Academiae Sinicae Edita 1979). Combining pharmaphylogeny analysis, we also believe that Hydrastis should be retained within the Ranunculaceae, congruent with the results of Ro and colleagues (1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichome types are therefore considered as important accessory characters, especially at lower taxonomic levels (e.g. Stebbins 1953;Faust & Jones 1973;Napp-Zinn & Eble 1980;Sahu 1982Sahu , 1984Hoot 1991;Al-Shamary & Gornall 1994;Korolyuk 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Vaidhya (2005). Polyporate pollen grains are considered to be secondarily derived one (Hoot, 1991). In most of the studied taxa are triporate, echinate exine wall.…”
Section: Resultsmentioning
confidence: 99%